Deteksi Kesuburan Perairan Aceh Menggunakan Citra Klorofil-A Satelit Aqua Modis - Mursyidin Mursyidin; Yuswardi Yuswardi (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
The fertility a body of water can be studied based of oceanographic parameters. The fertility of a body of water is closely related to high and low distribution of chlorophyll-a in the water High and low distribution of chlorophyll-a in a body of water can be studied by using satellite imagery. One of them by using satellite imagery Aqua Modis. Steps being taken: download imagery from MODIS website, cutting the image. Extract information from images, interpolation, and the division of classes. Aceh waters more fertile in June, July, and August compared to September and October. Aceh waters more fertile in the coastal area compared to the offshore area.